2017
DOI: 10.4149/neo_2017_210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MAGEA12 as a prognostic outlier gene in gastric cancers

Abstract: Melanoma antigen (MAGE) family genes are frequently over-expressed in a subset population of multiple cancers, and serve as idea therapeutic targets; however, their distribution pattern in gastric cancers has not yet been evaluated. In this study, we first performed a cancer outlier profile analysis (COPA) on a series of public gene expression datasets of gastric cancer, and identified MAGEA12 showing a significant outlier expression model reproducibly. We further in silico validated that MAGEA12 outlier over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…A previous report showed that overexpression of MAGEA6 is related to overall recurrence, but not each pattern of recurrence [35]. Furthermore, many studies have revealed that MAGEA protein expression, such as MAGEA1, A3, A6, A10, and A12, correlated with lymph node metastasis, advanced stage of cancer, and worse survival in gastric cancer [26,[35][36][37][38][39]. The present study showed a high incidence of hepatic recurrence and poor RFS in patients with positive MAGEA10 staining.…”
Section: Discussionmentioning
confidence: 43%
“…A previous report showed that overexpression of MAGEA6 is related to overall recurrence, but not each pattern of recurrence [35]. Furthermore, many studies have revealed that MAGEA protein expression, such as MAGEA1, A3, A6, A10, and A12, correlated with lymph node metastasis, advanced stage of cancer, and worse survival in gastric cancer [26,[35][36][37][38][39]. The present study showed a high incidence of hepatic recurrence and poor RFS in patients with positive MAGEA10 staining.…”
Section: Discussionmentioning
confidence: 43%
“…This problem is very relevant in cancer studies due to highly intra- and inter-tumour heterogeneity (Gyanchandani et al , 2016; Rubio-Perez et al , 2015). Interestingly, COPA method, after more than a decade from its publication, is still used to find outlier profiles due to its simplicity (Gaykalova et al , 2017; Teng et al , 2016; Wu et al , 2017), despite the fact that it is not the best method.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MAGE family proteins has been associated with the poor prognosis of many cancers in several studies. For example, MAGE-A12 was related to the high TNM staging of gastric cancer, and was demonstrated to be an independent indicator of poor prognosis in patients with gastric cancer (26). The expression of MAGE-A1-6 in the peritoneal lavage after gastric cancer surgery is correlated with the patient's reduced disease-free survival rate, indicating its association with tumor recurrence (27).…”
Section: Mage-c1mentioning
confidence: 99%